Exploring the role of locally-sourced ingredients in the rural hospitality system of Hungary - Csapody, Bence (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2024)
The aim of this research is to examine the role of local ingredients in the Hungarian rural hospitality system and to analyse the benefits and drawbacks of their utilization in restaurants. Previous literature lacks comprehensive studies investigating the use of local products in restaurants and the collaboration between producers and restaurants, particularly those employing qualitative methods involving both parties. To address this research gap, sixteen interviews were conducted with restaurant representatives and local producers. The findings of this research contribute to understanding the structural barriers hindering the effective integration of local products in restaurant operations. The study reveals that the dynamic nature of restaurant offerings relying on local ingredients, poses challenges for chefs, requiring constant innovation. Additionally, factors such as reliability, transparency, and hyper-local procurement strategies play crucial roles in the adoption of local products. However, logistics and communication emerge as significant shortcomings in restaurant-producer relations, and addressing these issues could improve efficiency, financial outcomes, and product quality. Furthermore, the study provides practical recommendations for enhancing the efficiency of short value chains and fostering mutual understanding between producers and restaurants.